Maize diversification and nitrogen fertilization effects on soil nitrous oxide emissions in irrigated mediterranean conditions - Franco-Luesma, Samuel; Lafuente, Victoria; Alonso-Ayuso, María; Bielsa, Ana; Kouchami-Sardoo, Iraj; Arrúe, José Luis; Álvaro-Fuentes, Jorge (Frontiers in Environmental Science, 2022)
Maize is a major irrigated crop in Mediterranean areas and its typical intensive management may impact soil nitrous oxide (N2O) emissions. In these irrigated continuous maize systems, the legumes incorporation as well as adjusted nitrogen (N) fertilization might be interesting strategies to reduce soil N2O emissions. The objective of this study was to assess the impact of cropping diversification and different N rates on soil N2O emissions in flooded irrigated maize under Mediterranean conditions. To achieve this, two cropping systems (maize monoculture system, MC; and pea -maize rotation, MP) and 3N rates (unfertilized, 0N; medium rate, MN; and high rate, HN) were evaluated in a field experiment established in NE Spain during 2 years (2019; 2020). During the studied period, the N rate had a significant effect on soil N2O emissions, with a non-linear positive response of cumulative soil N2O emissions to N rates. In both systems, quick and high increases of soil N2O fluxes were observed immediately after the N application reaching 55 and 100 mg N2O-N m−2 day−1 in MC and MP, respectively. Both years, the pea phase of the MP rotation showed greater cumulative N2O emissions than the fallow of MC. However, N2O losses in the maize phase were similar (2019) or even higher (2020) in MC than in MP. Moreover, in both seasons, the MN treatments showed lower yield-scaled N2O emissions and N emission factor than the HN treatments, being this last lower than 1% in all cases. The results obtained showed that in irrigated Mediterranean conditions the replacement of a fallow by a legume, together with an adjusted N fertilization are favourable strategies to mitigate soil N2O emissions in high-yielding maize systems.